ANALISIS PERMINTAAN SEMBAKO DI BULAN SUCI RAMADHAN: (Studi Kasus di Pasar Baru Cikatomas 2022-2024) - Novia Tia Tanjung; Mardani, Dede Aji (LPPM IAIT, 2024)
The purpose of this study was to determine the analysis of basic food demand in the holy month of Ramadhan (Case Study at Baru Market Cikatomas 2022-2024). The method used is qualitative research. The sample in this study were market traders in Cikatomas. The sampling technique used Snowball Sampling technique, This study explores the factors that cause the increase in basic food prices during the month of Ramadhan, focusing on the seasonal increase in demand. The study found that price spikes are caused by the tradition of preparing special dishes, increased income, as well as other factors such as production and distribution costs and import policies. After periods of peak demand, prices tend to stabilize or decline. Changes in consumption patterns and cultural values also affect the price dynamics of groceries, with consumers tending to buy high-quality foodstuffs during the holy month despite the increased prices. The study identified that factors such as price speculation by large traders and increased consumption of chicken meat and eggs contributed to the price spike. The findings illustrate how cultural and social values influence consumption patterns and prices of basic food items during these special periods, and provide insights into how price fluctuations can be managed by considering seasonality, production and distribution factors.